Cyclophilin A causes severe fever with thrombocytopenia syndrome virus-induced cytokine storm by regulating mitogen-activated protein kinase pathway - Huang, Huaying; Jin, Ke; Ouyang, Ke; Jiang, Zhengyi; Yang, Zhan; Hu, Nannan; Dai, Yan; Zhang, Yaqin; Zhang, Qian; Han, Ying; Zhao, Jie; Lin, Hong; et al. (Frontiers in Microbiology, 2022)
Severe fever with thrombocytopenia syndrome (SFTS) has become a global threat to public health since its first report in China in 2009. However, the pathogenesis of SFTS virus (SFTSV) in humans remains unclear. Also, there are no effective therapeutics for SFTS. Cyclophilin A (CyPA) regulates protein folding and trafficking involved in various viral infectious diseases, but its role in SFTSV infection has not been elucidated. Thus, this study aimed to elucidate the role of CyPA in SFTS pathogenesis. We found that plasma CyPA detection levels were elevated in patients with SFTS in the multi-organ dysfunction (MOD) phase. SFTSV-induced extracellular CyPA (eCyPA) was detected in THP-1 cells and normal human peripheral blood mononuclear cells (PBMCs) by ELISA. The eCyPA mediated the phosphorylation of the Mitogen-activated protein kinase (MAPK) pathway and the activation of NF-κB. The interaction between CypA and CD147 was validated by human recombinant CyPA (hrCyPA) and the CD147 inhibitor. We used an SFTSV infection and a lethal mouse model to demonstrate the therapeutic role of CyPA inhibitor Cyclosporine A (CsA) during SFTSV infection. Together, our results indicate that CyPA is associated with SFTSV-induced cytokine storm, which can be a potential target for SFTS therapy.